2023
DOI: 10.1111/php.13770
|View full text |Cite
|
Sign up to set email alerts
|

Redaporfin Development for Photodynamic Therapy and its Combination with Glycolysis Inhibitors

Abstract: Photodynamic therapy (PDT) remains an underutilized treatment modality in oncology. Many efforts have been dedicated to the development of better photosensitizers, better formulations and delivery methods, rigorous planning of light dose distribution in tissues, mechanistic insight, improvement of treatment protocols and combinations with other therapeutic agents. Hopefully, progress in all these fields will eventually expand the use of PDT. Here we offer a brief review of our own contribution to the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition, Karwicka et al found that depriving the tumor of blood supply using this PS molecule led to a highly effective antineoplastic response in vivo , with tumors not reappearing in 67% of mice after more than a year [ 207 ]. Lastly, Mendes and Arnaut explored the potential of combining Redaporfin with glycolysis inhibitors 3-bromopyruvate and 2-deoxyglucose [ 208 ] ( Figure 9 ). The authors explain that glucose transporters serve cells to absorb glucose and 2-deoxyglucose, which is analogous to glucose but cannot be metabolized.…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Karwicka et al found that depriving the tumor of blood supply using this PS molecule led to a highly effective antineoplastic response in vivo , with tumors not reappearing in 67% of mice after more than a year [ 207 ]. Lastly, Mendes and Arnaut explored the potential of combining Redaporfin with glycolysis inhibitors 3-bromopyruvate and 2-deoxyglucose [ 208 ] ( Figure 9 ). The authors explain that glucose transporters serve cells to absorb glucose and 2-deoxyglucose, which is analogous to glucose but cannot be metabolized.…”
Section: N -Heterocyclic-bearing Dyes As Photodynamic Therap...mentioning
confidence: 99%
“… Role of glycolysis inhibitors combined with the photodynamic activity of Redaporfin in developing an efficient antitumor strategy proposed by Mendes and Arnaut [ 208 ]. 2-Deoxyglucose acts as an inhibitor of hexokinase and phosphoglucose isomerase, while 3-bromopiruvato is uptaken by cells through monocarboxylate transporters, which are overexpressed in tumor cells, targeting hexokinase and glyceraldehyde-3-phosphate dehydrogenase enzymes, both of which are decisive for the glycolytic pathway’s regulation.…”
Section: Figurementioning
confidence: 99%